The effect of head roll and soft surface on Virtual SVV in healthy subjects: A normalization study - Necdet Ardıç, Fazıl; Şentürk, Murat; Çil, Taylan (ENT Updates, 2020)
Objective: The utricle is a crucial structure for a sense of gravity, but the contribution of proprioceptive receptors is also essential. This study aimed to measure the effect of head roll and soft surface on subjective visual vertical (SVV) in healthy subjects to determine the effect of neck and plantar proprioceptive inputs. Methods: In the first experiment, 78 healthy subjects performed 0, 15, 30, and 45-degree head rolls to the left and right side while standing. Three measurements were performed in every position. In the second experiment, 40 healthy subjects performed the same head maneuvers on a 20 cm thick soft surface. The Virtual SVV system (Virtual SVVTM, Interacoustics, Denmark) was utilized for all measurements. Results: The mean SVV on a hard surface was -0.99±2.34 degree at 0°. The SVV deviation increased with increasing head roll angle. The head roll to the right on a hard surface resulted in significantly different SVV angles than the neutral position (p0.05). SVV deviation increased on the soft surface. Nevertheless, there was no significant difference between the two surface conditions. Conclusion: The new Virtual SVV system measures SVV accurately. SVV deviation in the neutral position is similar to published results. However, under stress conditions such as with head roll and on a soft surface, every clinic has to set their normative data before comparing patients.